2013
DOI: 10.5489/cuaj.758
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of angiomyolipoma at a tertiary care centre: the decision between surgery and angioembolization

Abstract: E138Cite as: Can Urol Assoc J 2011;5(6):E138-E141; http://dx.doi.org/10.5489/cuaj.10028. Epub 2011 Jan 13. AbstractBackground: Angiomyolipoma (AML) is a benign renal neoplasm. First-line therapy includes renal preserving surgery or angioembolization (RAE), both with good outcomes in isolated studies. However, there are no comparative randomized trials and no clinical guidelines to help clinicians decide between these treatment modalities. Our study examines the patterns of AML treatment at a tertiary care cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…With improvement of cross sectional imaging and even in cases of low-fat tumors, AMLs can now be confidently diagnosed with an MRI specificity of up to 99% (52,53 (25)(26)(27)36). Literature comparing nephrectomy and NSS with SAE in the management of AMLs is limited (3,8,55,56) with medical and economic analyses favoring embolization in symptomatic renal AMLs or AMLs at risk of complications. Endovascular therapy for AMLs has less postoperative morbidity (6.9%) compared to partial nephrectomy (12%), with minimal invasiveness and shorter hospitalization (54,57).…”
Section: Discussionmentioning
confidence: 99%
“…With improvement of cross sectional imaging and even in cases of low-fat tumors, AMLs can now be confidently diagnosed with an MRI specificity of up to 99% (52,53 (25)(26)(27)36). Literature comparing nephrectomy and NSS with SAE in the management of AMLs is limited (3,8,55,56) with medical and economic analyses favoring embolization in symptomatic renal AMLs or AMLs at risk of complications. Endovascular therapy for AMLs has less postoperative morbidity (6.9%) compared to partial nephrectomy (12%), with minimal invasiveness and shorter hospitalization (54,57).…”
Section: Discussionmentioning
confidence: 99%
“…11 Many centers now favor transarterial embolization of angiomyolipoma, and reserve surgery for patients with refractory symptoms, complex renal artery anatomy, failure of embolization, and rare cases of diagnostic uncertainty. 12 The adoption of embolization as the treatment of choice has not been paralleled by a strengthening of the evidence supporting its use. Small studies, primarily case series report embolization as the sole form of therapy has a reported success of 86-90%, with a morbidity of 10-17%.…”
Section: Current Management Strategies Of Angiomyolipomamentioning
confidence: 99%
“…The mass appears to be echogenic on ultrasound and has the density of fat on CT scanning. When the diameter of renal AML becomes >4 cm, particularly for giant tumors with persistent hemorrhage or suspicion of malignancy, partial or total nephrectomy is the treatment of choice (11). In the present case, total nephrectomy was performed as the left kidney was non-functional.…”
Section: Discussionmentioning
confidence: 99%